Numerical Simulation of Liquid-Solid Coupling in Multi-Angle Fractures in Pressure-Sensitive Reservoirs - Feng, Yueli; Liu, Yuetian; Mao, Xiaolong; Chen, Jian (Fluid dynamics & materials processing, 2022)
This study clarifies the seepage characteristics of complex fractured pressure-sensitive reservoirs, and addresses a common technological problem, that is the alteration of the permeability degree of the reservoir bed (known to be responsible for changes in the direction and velocity of fluid flows between wells). On the basis of a new pressure-sensitive equation that considers the fracture directional pressure-sensitive effect, an oil-gas-water three-phase seepage mathematical model is introduced, which can be applied to pressure-sensitive, full-tensor permeability, ultralow-permeability reservoirs with fracture-induced anisotropy. Accordingly, numerical simulations are conducted to explore the seepage laws for ultralow-permeability reservoirs. The results show that element patterns have the highest recovery percentage under a fracture angle of 45°. Accounting for the pressure-sensitive effect produces a decrease in the recovery percentage. Several patterns are considered: inverted five- seven- and nine-spot patterns and a cross-row well pattern. Finally, two strategies are introduced to counteract the rotation of the direction of the principal permeability due to the fracture directional pressure-sensitive effect.